Necrotizing Enterocolitis: An Update on the Benefits of Breast Milk - Khader, Adam; Gallagher, Julie; Woods, Megan; Yang, Weng-Lang; Wang, Ping; Stylianos, Steven; Prince, Jose M. (International Journal of Child Health and Nutrition, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Necrotizing enterocolitis (NEC) is the leading cause of death for preterm infants resulting from gastrointestinal disease. This review will focus on several components of human breast milk that may be beneficial in the prevention and treatment of NEC. The severe pathological features of NEC include inflammation, mucosal ulceration and disruption of the intestinal barrier. Despite maximal neonatal intensive care, the incidence and mortality rate of the disease remains high. Administration of breast milk, as well as donor breast milk, to preterm infants has been shown to reduce the incidence of NEC. Beyond this, there is no disease specific treatment for NEC. The immunomodulatory and protective properties of human breast milk have been evaluated in search of key components that may be utilized for the effective prevention and treatment of NEC.